Política de saúde: análise da implantação do NASF e o trabalho interdisciplinar da equipe multiprofissional do NASF no município de Medianeira - Canton, Pamella Regina da Cruz (2021)
This dissertation sought to analyze the historical process of health policy, with the aim of investigating the emergence and development of the NASF, as an equipment within the scope of the family health strategy. Exposing the legal contribution for its implementation, as a strategy for the program's performance, making an analytical approach to the interdisciplinary work of the NASF multidisciplinary team, based on the framework and conceptual of interdisciplinary work, seeking to capture the challenges and potentials found in the interventions of the multidisciplinary team of the NASF, facing the implementation of this social policy and facing the reality of the municipality of Medianeira in the State of Paraná. In this sense, studies within the scope of health policy have been analyzing the practices, the quality of care, the resoluteness of the actions implemented, the expectations of users, as well as the discussion with the professions that guide the policy, and the relevant role that the multidisciplinary teams have been expanding in recent years. Health came to be understood beyond the absence of disease, where non-biological determinants also influence the health-disease process. Creating opportunities for change in the health care model, removing the focus from biomedical care, seeking broad actions that meet all the determinants that influence the health-disease process, carrying out prevention and health promotion actions, focusing on the best quality of care offered by Health professionals. It is important to articulate collective health activities together with clinical care interventions in primary care services. Thus, implementing the NASF service - Extended Family Health Nucleus, a strategy is adopted to achieve the goals of primary health care, the service is considered an instrument that will help in changing attitudes in the performance of health professionals in the family. As it is a service in which, despite the conceptual bases already discussing the principles that have guided it since the federal constitution, its implementation in small municipalities was recent. In this sense, there is a discrepancy regarding the organizational structure, human resources and the role of professionals in the multidisciplinary team of the NASF, in relation to what is theoretically foreseen, as well as what is materialized in the daily practice of the municipalities, that is, between how it is being implemented and how it was typified, both by professionals and by the municipal administration. It appears that in daily practice it is not being carried out as established in the legislation, and that several factors contribute to this problem, ranging from municipal management factors, such as insufficient funding, lack of human resources, as well as lack of training, specific professional training, communication difficulties, etc. However, despite the numerous challenges posed to the effectiveness and efficiency of the NASF, it is still necessary to seek to work on health issues in accordance with the SUS assumptions, the largest of which is acting with a view to overcoming the SUS legal and the real SUS.